Enhancer Hijacking Drives Oncogenic BCL11B Expression in Lineage-Ambiguous Stem Cell Leukemia - Montefiori, Lindsey E; Bendig, Sonja; Gu, Zhaohui; Chen, Xiaolong; Pölönen, Petri; Ma, Xiaotu; Murison, Alex; Zeng, Andy; Garcia-Prat, Laura; Dickerson, Kirsten; Iacobucci, Ilaria; Abdelhamed, Sherif; et al. (Cancer discovery, 2021)
Lineage-ambiguous leukemias are high-risk malignancies of poorly understood genetic basis. Here, we describe a distinct subgroup of acute leukemia with expression of myeloid, T lymphoid, and stem cell markers driven by aberrant allele-specific deregulation of , a master transcription factor responsible for thymic T-lineage commitment and specification. Mechanistically, this deregulation was driven by chromosomal rearrangements that juxtapose to superenhancers active in hematopoietic progenitors, or focal amplifications that generate a superenhancer from a noncoding element distal to . Chromatin conformation analyses demonstrated long-range interactions of rearranged enhancers with the expressed allele and association of with activated hematopoietic progenitor cell -regulatory elements, suggesting BCL11B is aberrantly co-opted into a gene regulatory network that drives transformation by maintaining a progenitor state. These data support a role for ectopic expression in primitive hematopoietic cells mediated by enhancer hijacking as an oncogenic driver of human lineage-ambiguous leukemia. SIGNIFICANCE: Lineage-ambiguous leukemias pose significant diagnostic and therapeutic challenges due to a poorly understood molecular and cellular basis. We identify oncogenic deregulation of driven by diverse structural alterations, including superenhancer generation, as the driving feature of a subset of lineage-ambiguous leukemias that transcend current diagnostic boundaries. .